2021
DOI: 10.1038/s41598-021-99424-4
|View full text |Cite
|
Sign up to set email alerts
|

Age estimation using methylation-sensitive high-resolution melting (MS-HRM) in both healthy felines and those with chronic kidney disease

Abstract: Age is an important ecological tool in wildlife conservation. However, it is difficult to estimate in most animals, including felines—most of whom are endangered. Here, we developed the first DNA methylation-based age-estimation technique—as an alternative to current age-estimation methods—for two feline species that share a relatively long genetic distance with each other: domestic cat (Felis catus; 79 blood samples) and an endangered Panthera, the snow leopard (Panthera uncia; 11 blood samples). We measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 46 publications
1
42
0
Order By: Relevance
“…We selected target genomic locations adjacent to 12 genes, namelyGSE1 , VGF , SLC12A5 , SCGN , KCNK12 ,OTUD7A , BCL6B , POU4F2 , ELOVL2 , RALYL ,KISS1R , and CAPS2 (Table 1). The methylation levels of CpG sites adjacent to these genes change with age in humans (Day et al 2013;Florath et al 2014;Bekaert et al 2015;Lowe et al 2018), dogs (Ito et al 2017;Yamazaki et al 2021), and cats (Qi et al 2021). We identified homologous sequences in the genomic regions of brown bears containing the target CpG sites using the Basic Local Alignment Search Tool (BLAST) provided by the National Center for Biotechnology Information.…”
Section: Selection Of Target Genomic Locationsmentioning
confidence: 99%
See 2 more Smart Citations
“…We selected target genomic locations adjacent to 12 genes, namelyGSE1 , VGF , SLC12A5 , SCGN , KCNK12 ,OTUD7A , BCL6B , POU4F2 , ELOVL2 , RALYL ,KISS1R , and CAPS2 (Table 1). The methylation levels of CpG sites adjacent to these genes change with age in humans (Day et al 2013;Florath et al 2014;Bekaert et al 2015;Lowe et al 2018), dogs (Ito et al 2017;Yamazaki et al 2021), and cats (Qi et al 2021). We identified homologous sequences in the genomic regions of brown bears containing the target CpG sites using the Basic Local Alignment Search Tool (BLAST) provided by the National Center for Biotechnology Information.…”
Section: Selection Of Target Genomic Locationsmentioning
confidence: 99%
“…To evaluate whether age, sex, or growth environment affects the deviation of the age estimation model, linear regressions were generated using Δage (predicted age -chronological age) and |Δage| (absolute difference between predicted age and chronological age) as dependent variables and three factors, as well as the interactions among each factor pair, as explanatory variables (Qi et al 2021). Model construction and selection were conducted using the "lm" command and "MnMIn" package in the R software.…”
Section: Age Estimation Model and Model Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…a*M100Mgoodbreak=DfDfmaxDf$$ \frac{a^{\ast }M}{100-M}=\frac{\mathrm{Df}}{{\mathrm{Df}}_{\mathrm{max}}-\mathrm{Df}} $$where “ a ” is a coefficient, M is the methylation level of each standard sample, Df is the Df value for each standard sample, and Df max is the maximum Df value for the 100% methylated standard. The “nls” function in R 4.2.1 was used to implement the regression model and calculate the estimated value of “ a ” as in Qi et al (2021). Typical standard curves for NR1D1 and CLDN22 are shown in Figure A5 in Appendix .…”
Section: Methodsmentioning
confidence: 99%
“…Most importantly, many studies have reported correlations between DNA methylation levels at speci c CpG islands in certain genes and age, mainly in humans [19,[28][29][30]. However, recently, increasing numbers of studies on other species have been carried out, such as in dogs (Canis familiaris) [31], cats (Felis catus) [32], chimpanzees (Pan troglodytes) [33], bats (Myotis bechsteinii) [34,35], seabirds (Ardenna tenuirostris) [36], green turtles (Chelonia mydas) [37], sh [38,39], and several cetacean species [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%